OXIDATIVE STRESS IN THE PATHOGENESIS OF VITILIGO - DR.D. MADHAVI; DR.T.E.DIVYAMALINI; DR.C.V.SARADA (International Journal of Pharma and Bio Sciences, 2014)
Vitiligo - specific, common, often heritable, acquired disorder characterized by circumscribed milky white cutaneous macules.. The disease shows no racial/gender predilection and can occur at any age. The incidence is found to be 1-2%. Among the various theories available for explaining the pathogenesis of vitiligo, this study evaluates the role of oxidative stress in the disease pathogenesis In this study 100 cases of vitiligo patients were evaluated in two age groups as follows Children (8-17 years) Young adults(18-30years) Serum levels of malondialdehyde, catalase, zinc were estimated in these patients. The values of these parameters were compared with 100 healthy controls who were grouped in the same way as cases on the basis of age. There was a statistically significant increase in serum malondialdehyde and decrease in serum catalase and serum zinc in the both groups of cases as compared to their age based controls. Thus it can be concluded that oxidative stress is the primary and also the major factor contributing to the pathogenesis of vitiligo. Thus the use of antioxidant therapy in vitiligo patients could yield a better outcome in this psychologically disturbing depigmenting disorder